Toward Efficient Electrocatalytic Oxygen Evolution: Emerging Opportunities with Metallic Pyrochlore Oxides for Electrocatalysts and Conductive Supports - Kim, Myeongjin; Park, Jinho; Kang, Minsoo; Kim, Jin Young; Lee, Seung Woo (AMER CHEMICAL SOC, 2020)
The design of active and stable electrocatalysts for oxygen evolution reaction is a key enabling step toward efficient utilization of renewable energy. Along with efforts to develop high-performance electrocatalysts for oxygen evolution reaction, pyrochlore oxides have emerged as highly active and stable materials that function as catalysts as well as conductive supports for hybrid catalysts. The compositional flexibility of pyrochlore oxide provides many opportunities to improve electrocatalytic performance by manipulating material structures and properties. In this Outlook, we first discuss the recent advances in developing metallic pyrochlore oxides as oxygen evolution catalysts, along with elucidation of their reaction mechanisms, and then introduce an emerging area of using pyrochlore oxides as conductive supports to design hybrid catalysts to further improve the OER activity. Finally, the remaining challenges and emerging opportunities for pyrochlore oxides as electrocatalysts and conductive supports are discussed.